Vengeance - Mocan, Naci (The Review of Economics and Statistics, 2013)
This paper investigates the extent of vengeful feelings and their determinants using data on more than 116,000 individuals from 66 countries. Country characteristics as well as personal attributes of the individuals influence vengeful feelings. The magnitude of vengeful feelings is greater for people in countries with low levels of education, low-income countries, and interrupted democracies. Personal education has an impact on vengeful feelings in lower-income countries. The results suggest that some puzzles about individual choice can best be explained by considering the interplay of personal and economic factors.